2023
DOI: 10.22317/jcms.v9i1.1321
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of missing opportunity of vaccination at primary health care center: A retrospective study

Abstract: Objectives: The study aim is to assess the vaccination status of children under two years old in Al-Asatetha primary health care center / Hilla-Iraq. Method: Retrospective study design (Retrospective chart review) was used to assess the missed opportunities of vaccination for children under the age of two years by reviewing their immunization status from medical reports at the primary health care center. The purposive sampling was used to collect the data of 1000 children born from 1-1-2020 to 31-12-2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
4
0
2
Order By: Relevance
“…This study revealed that the MOI prevalence was increased among children whose families with increasing number and birth order. This finding was in agreement with other studies [21,31,35] . This finding could be due to an increase in caregiver's experience with increasing number of children.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This study revealed that the MOI prevalence was increased among children whose families with increasing number and birth order. This finding was in agreement with other studies [21,31,35] . This finding could be due to an increase in caregiver's experience with increasing number of children.…”
Section: Discussionsupporting
confidence: 94%
“…Among the Iraqi studies, this finding was relatively consistent with previous study conducted in Baghdad (36.4%) [14] , in Diyala province/Iraq (30%) [15] , and that reported by UNICEF-Iraq-Statistics 2015 (28%) [16] . However, our finding was higher than that reported in other previous studies conducted in Baghdad (11-22.3%) [17][18][19] and lower than that reported in other Iraqi Provinces as in Mosul (45.8%) [20] and Babylon (61%) [21] . The present study revealed that 68.4% of the respondents were completely immunized.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…The highest percent of treatment success occurs in EPTB patients. In Ethiopia, the treatment success rates were 89.2%, 83.3% and 81.9% among PTB+, PTB-and EPTB patients, respectively (Gebrezgabiher et al, 2016), This agreed with another study which revealed that the highest percentage of successful treatment was among PTB (Obaid et al, 2023).…”
Section: Tablesupporting
confidence: 85%